The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/09297049.2018.1441820
|View full text |Cite
|
Sign up to set email alerts
|

Basic visual perceptual processes in children with typical development and cerebral palsy: The processing of surface, length, orientation, and position

Abstract: The present study aims to assess how the processing of basic visual perceptual (VP) components (length, surface, orientation, and position) develops in typically developing (TD) children (n = 215, 4-14 years old) and adults (n = 20, 20-25 years old), and in children with cerebral palsy (CP) (n = 86, 5-14 years old) using the first four subtests of the Battery for the Evaluation of Visual Perceptual and Spatial processing in children. Experiment 1 showed that these four basic VP processes follow distinct develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…For example, position errors, e.g. selecting blocks from the wrong place, were more common in the younger children of the CP group, indicating visual spatial memory difficulties, whilst the older children in the CP group were more likely to have problems with sequencing skills (also see Schmetz et al, 2018). Corsi type tasks are of relevance to mathematical ability as the visual spatial sketchpad may be used as a 'mental blackboard' (Baddeley, 2007) when distinguishing between different mathematical forms and shape, as well as retaining previous visual information (see Hubber, Gilmore, & Cragg, 2014).…”
Section: Mathematical Abilities Visual-spatial Abilities and Cerebrmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, position errors, e.g. selecting blocks from the wrong place, were more common in the younger children of the CP group, indicating visual spatial memory difficulties, whilst the older children in the CP group were more likely to have problems with sequencing skills (also see Schmetz et al, 2018). Corsi type tasks are of relevance to mathematical ability as the visual spatial sketchpad may be used as a 'mental blackboard' (Baddeley, 2007) when distinguishing between different mathematical forms and shape, as well as retaining previous visual information (see Hubber, Gilmore, & Cragg, 2014).…”
Section: Mathematical Abilities Visual-spatial Abilities and Cerebrmentioning
confidence: 99%
“…Researchers comment on the paucity of investigations into numerical and arithmetic abilities of children with CP particularly those involving aspects of visual-spatial perception (Schmetz, Magis, Detraux, Barisnikov, & Rousselle, 2018;van Rooijen et al, 2012). Available research has shown that children with CP are more likely to experience difficulties with mathematical learning than TD children (Frampton, Yude, & Goodman, 1998), and a small number of studies have highlighted that children with CP are often delayed in acquiring numerical skills such as: subitizing (quantifying sets); counting; and basic arithmetic problem-solving (Jenks, van Lieshout, & de Moor, 2012;van Rooijen et al, 2012).…”
Section: Mathematical Abilities Visual-spatial Abilities and Cerebrmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we observed that fatigue might be a problem, so we decided to split the tasks in three phases, which further lengthened the time of data collection. Moreover, a recent study by Schmetz et al (2018) assessed how basic visual processes progress in 215 children from 4 to 14 years old and in 20 adults. The results showed that processing of surfaces reached maturity by the age of 9–10 years, processing of length and position by the age of 13–14 years, and orientation processing continues to improve beyond the age of 14 years.…”
Section: Methodsmentioning
confidence: 99%
“…Visual perceptual ability is one of the many areas that is often impaired in children with CP. Schmetz et al 2 confirmed that children with CP aged 5-18 years have persistent deficits in visual perception or visual perceptual impairment (VPI) compared to typical children of similar age and nonverbal IQ 2 .…”
Section: Introductionmentioning
confidence: 98%